2010
DOI: 10.1007/s00424-010-0786-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction: a strategic target in the treatment of hypertension?

Abstract: Endothelial dysfunction is a common feature of hypertension, and it results from the imbalanced release of endothelium-derived relaxing factors (EDRFs; in particular, nitric oxide) and endothelium-derived contracting factors (EDCFs; angiotensin II, endothelins, uridine adenosine tetraphosphate, and cyclooxygenase-derived EDCFs). Thus, drugs that increase EDRFs (using direct nitric oxide releasing compounds, tetrahydrobiopterin, or L-arginine supplementation) or decrease EDCF release or actions (using cyclooxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
121
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(132 citation statements)
references
References 91 publications
(131 reference statements)
6
121
0
2
Order By: Relevance
“…Particularly, dihydropyridine, can reverse the impaired endothelium-dependent vasodilation impaired in different places, including subcutaneous, epicardial, renal circulation and forearm. On forearm circulation, Nifedipine and Lacidipine can improve endothelial dysfunction, restoring the NO availability through a mechanism that is likely related to an antioxidant effect (25) .…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, dihydropyridine, can reverse the impaired endothelium-dependent vasodilation impaired in different places, including subcutaneous, epicardial, renal circulation and forearm. On forearm circulation, Nifedipine and Lacidipine can improve endothelial dysfunction, restoring the NO availability through a mechanism that is likely related to an antioxidant effect (25) .…”
Section: Discussionmentioning
confidence: 99%
“…In many forms of human and experimental hypertension, endothelial dysfunction and arterial remodeling are considered key players in the development and maintenance of high blood pressure. [3][4][5] In spontaneously hypertensive rats (SHR) a well-described manifestation of endothelial dysfunction is an increased production of endotheliumderived contractile factors (EDCF). 6 Drug-intervention studies have shown that some anti-hypertensive treatments, for instance with angiotensin AT 1 receptor antagonists, not only lower blood pressure but also cause an improvement of endothelial function and regression of structural changes in resistance arteries.…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact molecular mechanism of hypertension remains unknown. It has been suggested that increased blood pressure is probably the reason or/and result of vascular endothelial dysfunction [2]. Vascular endothelium plays an important role in the regulation of blood pressure by secreting various vasoactive substances.…”
Section: Introductionmentioning
confidence: 99%